Dementia as a disease of old age - Węgrzyn, Magdalena; Kubiak, Karolina; Olesinkiewicz, Kinga; Lamtych, Martyna; Bednarek, Hanna; Kwiatkowska, Klaudia; Dorobiala, Jakub; Włoch, Agata; Sochań, Agata (Journal of Education, Health and Sport, 2019)
Background: The increase in chances of dementia with age translates into huge numbers of patients. Her diagnosis is often difficult to indicate and treatment is still about fighting the symptoms and not the disease itself. Material and methods: A review of the literature and WHO research was carried out indicating the greater progression of the disease in old age and the stages of the course of the disease. Results and conclusions:The disease progresses gradually and it is very difficult to make a correct diagnosis in the early stadium. There are various ways to diagnose dementia, but doctors still have a major role to do in close contact with the patient. Rapid diagnosis can significantly slow down the disease, but it cannot be cured completely.